Adherence, virological and immunological outcomes for HIV-infected veterans starting combination antiretroviral therapies. - Braithwaite, R Scott; Kozal, Michael J; Chang, Chung Chou H; Roberts, Mark S; Fultz, Shawn L; Goetz, Matthew Bidwell; Gibert, Cynthia; Rodriguez-Barradas, Maria; Mole, Larry; Justice, Amy C (AIDS (London, England), 2007)
We aimed to determine adherence, virological, and immunological outcomes one year after starting a first combination antiretroviral therapy (ART) regimen.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Benzoxazines; CD4 Lymphocyte Count; Cohort Studies; Drug Administration Schedule; Female; HIV Infections; HIV-1; Humans; Male; Middle Aged; Patient Compliance; Reverse Transcriptase Inhibitors; RNA, Viral; Treatment Outcome; Veterans; Viral Load